Human Umbilical Cord Mesenchymal Stem Cell-Derived Extracellular Vesicles Carrying MicroRNA-29a Improves Ovarian Function of Mice with Primary Ovarian Insufficiency by Targeting HMG-Box Transcription Factor/Wnt/β-Catenin Signaling. (2nd July 2022) - Gao, Tian; Cao, Yi; Hu, Min; Du, Ying
Abstract : Background . Primary ovarian insufficiency (POI) is a female disease characterized by ovarian function loss under 40 years old. Transplantation of exosomes is an encouraging regenerative medicine method that has the potential for restoring ovarian functions post-POI with high efficiency. Therefore, we investigate the therapeutic efficacy and potential mechanisms of human umbilical cord mesenchymal stem cell- (UCMSC-) derived exosomes on ovarian dysfunction post-POI. Methods . The model of POI was established by intraperitoneal injection with 5 mg/kg cisplatin. The mouse ovarian function was detected by measuring the levels of anti-Mullerian hormone, follicle-stimulating hormone, and estradiol and detecting the morphological changes. For in vitro experiments, the characterization and identification of UCMSCs and UCMSC-derived exosomes were done by observation of morphologies and flow cytometry. To exclude the interference effect of nonspecific precipitation substances, UCMSCs were treated with RNase A or RNase A in combination with Triton X-100. Granulosa cell (GC) identification was performed using immunofluorescence. GC proliferation and viability were assessed using 5-ethynyl-2 ′ -deoxyuridine (EdU) assays and Cell Counting Kit-8 (CCK-8), and GC apoptosis was calculated by flow cytometry. Gene expression and protein levels were evaluated using reverse transcription quantitative polymerase chain reaction (RT-qPCR) and western blotting. The binding relationship between miR-29a and HMG-box transcription factor (HBP1) was verified by luciferase reporter assays. Results . In vitro, the human UCMSC-derived exosomes carrying miR-29a upregulation promoted the proliferation of GCs and suppressed their apoptosis. In vivo, miR-29a upregulation reserved the mature follicles and restored the ovarian functions. miR-29a targeted HBP1 and negatively regulated its expression. HBP1 upregulation rescued the miR-29a upregulation-induced inhibition in GC apoptosis and inactivated the Wnt/ β -catenin pathway. Conclusion . The exosomal miR-29a derived from human UCMSCs improves the ovarian function by targeting HBP1 and activating the Wnt/ β -catenin pathway.